1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Series & Integrals 2

  1. May 14, 2009 #1
    1. The problem statement, all variables and given/known data

    show what integral of 1/(1-xy)dxdy = pi2/6

    dx 0 to 1
    dy 0 to 1

    2. Relevant equations

    3. The attempt at a solution
  2. jcsd
  3. May 14, 2009 #2


    Staff: Mentor

    Doesn't look like a hard integral. What have you tried?
  4. May 14, 2009 #3
    [tex]\int[/tex]1/(1-xy)dx = ln(1-xy) = ln(1-y) - ln1

    [tex]\int[/tex]ln(1-y) - ln1 dy = (1-y)ln(1-y) - (1- y) - yln1

    = -ln1 - (ln1 - 1) = = -2ln1 + 1 huh
  5. May 14, 2009 #4

    [tex]\int[/tex]f '(x)/f(x) dx = ln[f(x)] for your 1st integral, also you're taking y constant, so treat it like one
  6. May 14, 2009 #5
    1/(1-xy) = sum from n= 0 to infinity of x^n y^n

    The integral is thus the sum from n = 0 to infinity of 1/(n+1)^2 which is pi^2/6
  7. May 14, 2009 #6


    User Avatar
    Homework Helper

    The first integration isn't correct. You can see that immediately by differentiating the primitive. Use a substitution if you don't see it right away, [itex]u=1-xy,du=-ydx[/itex]. The hard part comes after this however. Hint: Use the power series of the logarithm.

    Edit: Use Count's method it's quicker and easier.
  8. May 15, 2009 #7
    ok so your saying

    1(1-xy) = [tex]\sum[/tex]xnyn from n = 0 to infinity

    [tex]\int\int[/tex]1/(1-xy) = [tex]\sum[/tex]1/(n+1)2 = pi2/6

    how does 1/(1-xy) go to the sum of xnyn

    and how does 1/(1-xy) got to the sum of (n+1)2 then go to pi2/2
  9. May 15, 2009 #8


    User Avatar
    Homework Helper

    Ok let's say z=xy, then [tex] \frac{1}{1-xy}= \frac{1}{1-z}=\sum_{n=0}^\infty z^n=\sum_{n=0}^\infty (xy)^n=\sum_{n=0}^\infty x^n y^n[/tex]. Then you take the integral over the sum.

    [tex]\int_0^1 \int_0^1 \sum_{n=0}^\infty x^n y^n dxdy=\sum_{n=0}^\infty \left(\int_0^1 \int_0^1 x^n y^n dxdy\right)[/tex]. Can you see how to continue from here?

    Edit: I think you're expected to know that the series converges to pi^2/6 by heart. However http://en.wikipedia.org/wiki/Basel_problem shows you how to get to that value in case you're interested.
    Last edited: May 15, 2009
  10. May 15, 2009 #9
    oops i think i forgot something

    the entire problem is

    show that

    [tex]\int\int[/tex]1/(1-xy)dxdy = pi2/6

    by doing the double substitution

    x = (u - v)/[tex]\sqrt{2}[/tex] and y = (u + v)/[tex]\sqrt{2}[/tex]

    This amounts to rotating the axes cuonterclockwise through the angle pi/4
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook